A tool for mapping rural-urban interfaces on different scales, in Advances in Forest Fire Research - Bouillon, Christophe (2014)
The aim of this paper is to present the methodologies, a software and results developed in the European FUME program to map the rural-urban interfaces (RUI). Three methodologies were set up for RUI mapping: two on the local scale (the community scale) and one on the global scale (the European scale). The first local scale method was developed in a French context by IRSTEA. In this case the RUI is defined by a radius of 100 metres around each house located at a distance inferior to 200 metres from forests or scrublands. The building density was used to create four classes of housing configuration. Then the structure of vegetation was characterized and mapped to emphasize its horizontal continuity with landscape ecology metrics. The RUI map was created by a combination of housing configuration and vegetation characterisation. The second local scale method developed by TRAGSATEC is based on three phases. First a settlement map creation with the union of a land use cover and a vegetation cover defines the housing and the landscape that surrounds them. Then a buffer is created around settlements which are located at a distance inferior to 400 m from the forest; its size depends on the difficulty in protecting the houses against fire. In the final phase the different types of RUI are defined from the type of settlement and vegetation-settlement connection around houses. The global scale method developed by IRSTEA makes possible the comparison of the situations and the importance of RUI in the different European countries. On the global scale, the rural urban interfaces are defined by a radius of 400 metres around houses located atless than 200 metres from forests or shrubland. The global rural urban interface map results from the combination of criteria from the Corine Land Cover database and from the soil sealing database. A major step of the work was the development of a software named RUImap with the three different methods above. The use of the tool could be very advantageous for fire risk analysis on RUI scale, and for local quantification of fuel charge and continuity. This information linked with the direct knowledge of the general context is very important for the local fire risk assessment.